2002
DOI: 10.1182/blood.v99.7.2599
|View full text |Cite
|
Sign up to set email alerts
|

Development of pancytopenia with neutralizing antibodies to thrombopoietin after multicycle chemotherapy supported by megakaryocyte growth and development factor

Abstract: Clinical trials of thrombopoietin (TPO), the central regulator of megakaryocytopoiesis, have revealed few side effects associated with its use. We here report a case of pancytopenia associated with the development of neutralizing antibodies to TPO that occurred in a patient who had undergone multicycle chemotherapy with multiple cycles of subcutaneous administration of pegylated recombinant human megakaryocyte growth and development factor. Samples of the patient's bone marrow showed trilineage hypoplasia with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
142
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(145 citation statements)
references
References 24 publications
0
142
2
1
Order By: Relevance
“…Indeed, patients who develop a neutralizing antibody to thrombopoietin eventually develop pancytopenia [10,34,35].…”
Section: Thrombopoietin Physiologymentioning
confidence: 99%
“…Indeed, patients who develop a neutralizing antibody to thrombopoietin eventually develop pancytopenia [10,34,35].…”
Section: Thrombopoietin Physiologymentioning
confidence: 99%
“…145 AEs associated with the use of rhTPO plus G-CSF appear to be similar to those seen with the use of G-CSF alone; 144,145 however, cytopenias owing to neutralizing antibodies to TPO have been reported in a small number of patients who were given rhTPO to treat chemotherapy-induced thrombocytopenia. 146,147 Currently, no TPOs have been approved by the FDA for mobilization. 148 Parathyroid hormone Parathyroid hormone (PTH) activates osteoblasts, which produce hematopoietic growth factors in the stem cell niche, thereby increasing the numbers of circulating stem cells.…”
Section: Novel Agentsmentioning
confidence: 99%
“…[41][42][43] Thrombopoietin, in addition to G-CSF during mobilization has been shown to increase the CD34 þ and CD34/ CD41a þ yields plus results in small but statistically significant improvements in platelet recovery after transplantation. 12,15,44,45 Clinical trials with thrombopoietin have been hampered, however, due to the development of neutralizing Ab and thrombocytopenia, 46,47 risk of thrombocytosis and thrombosis and need for co-administration with G-CSF. 12,15 This study has shown that pegfilgrastim increases CD34/CD41a þ cells in the peripheral blood, producing similar responses to filgrastim and that it is well tolerated.…”
Section: Discussionmentioning
confidence: 99%